The Effect of Intracellular Tacrolimus Exposure on Calcineurin Inhibition in Immediate- and Extended-Release Tacrolimus Formulations - Pere Fontova; Lisanne N. van Merendonk; Anna Vidal-Alabró; Raül Rigo-Bonnin; Gema Cerezo; Stefaan van Oevelen; Oriol Bestard; Edoardo Melilli; Nuria Montero; Ana Coloma; Anna Manonelles; Joan Torras; et al. (MDPI AG, 2023)
Despite intensive monitoring of whole blood tacrolimus concentrations, acute rejection after kidney transplantation occurs during tacrolimus therapy. Intracellular tacrolimus concentrations could better reflect exposure at the site of action and its pharmacodynamics (PD). Intracellular pharmacokinetic (PK) profile following different tacrolimus formulations (immediate-release (TAC-IR) and extended-release (TAC-LCP)) remains unclear. Therefore, the aim was to study intracellular tacrolimus PK of TAC-IR and TAC-LCP and its correlation with whole blood (WhB) PK and PD. A post-hoc analysis of a prospective, open-label, crossover investigator-driven clinical trial (NCT02961608) was performed. Intracellular and WhB tacrolimus 24 h time-concentration curves were measured in 23 stable kidney transplant recipients. PD analysis was evaluated measuring calcineurin activity (CNA) and simultaneous intracellular PK/PD modelling analysis was conducted. Higher dose-adjusted pre-dose intracellular concentrations (C0 and C24) and total exposure (AUC0-24) values were found for TAC-LCP than TAC-IR. Lower intracellular peak concentration (Cmax) was found after TAC-LCP. Correlations between C0, C24 and AUC0-24 were observed within both formulations. Intracellular kinetics seems to be limited by WhB disposition, in turn, limited by tacrolimus release/absorption processes from both formulations. The faster intracellular elimination after TAC-IR was translated into a more rapid recovery of CNA. An Emax model relating % inhibition and intracellular concentrations, including both formulations, showed an IC50, a concentration to achieve 50% CNA inhibition, of 43.9 pg/million cells.